Frequency of, and factors associated with, hepatitis B virus reactivation in hepatitis C patients treated with all‐oral direct‐acting antivirals: Analysis of a Japanese prospective cohort. Issue 13 (1st August 2017) - Doi, Akira; Sakamori, Ryotaro; Tahata, Yuki; Urabe, Ayako; Morishita, Naoki; Yamada, Ryoko; Furuta, Kunimaro; Kodama, Takahiro; Hikita, Hayato; Yakushijin, Takayuki; Ohkawa, Kazuyoshi; Kaneko, Akira; et al.
Abstract : Aim: Several case reports have shown that hepatitis B virus (HBV) reactivation developed in hepatitis C patients with a current or previous HBV infection during direct‐acting antiviral (DAA) treatment, which led to severe hepatitis or death in some cases. However, its precise frequency and risk factors are not entirely clear. We analyzed a prospective cohort. Methods: We analyzed HBV reactivation in 461 consecutive hepatitis C patients who received 12 weeks of ledipasvir/sofosbuvir for genotype 1 or sofosbuvir plus ribavirin for genotype 2 at multiple centers. Results: By the examination of the preserved sera at baseline, 159 patients (34%) were identified as seropositive for HBV core antibody (anti‐HBc) and were included in the subsequent analysis; 4 patients were positive for HBV surface antigen (HBsAg), and the others were negative. Serum HBV DNA was undetectable or was detectable but <20 IU/mL at baseline for all patients. Serial measurement of HBV DNA at 4 weeks and 12 weeks in the preserved serum samples was available in 147 patients and identified HBV reactivation (defined as the appearance of serum HBV DNA ≥20 IU/mL) in 2 HBsAg‐positive and 3 HBsAg‐negative patients. No patient developed HBV‐associated hepatitis. Patients who developed HBV reactivation had significantly lower anti‐HBs titers and higher serum alanine transferase levels before treatment. Conclusion: Hepatitis B virus reactivation during direct‐acting antiviral therapies occurs in 3.4% (5/147) of patients who are positive for anti‐HBc. A low titer of anti‐HBs and a high serum alanine transferase level prior to treatment are associated with reactivation in this patient group.